Cytokines and oxidative stress status following a handball game in elite male players - Popp Marin, D.; de Cassia Macedo dos Santos, R.; Bolin, A. P.; Alves Guerra, B.; Hatanaka, E.; Otton, R. (Oxidative Medicine and Cellular Longevity, 2011)
Background. Handball is considered an intermittent sport that places an important stress on a player's aerobic and anaerobic metabolism. However, the oxidative stress responses following a handball game remain unknown. We investigated the responses of plasma and erythrocyte antioxidant system and oxidative stress biomarkers following a single handball game. Methods. Fourteen male elite Brazilian handball athletes were recruited in the present study. Blood samples were taken before, immediately, and 24 hours after the game. Results. After the game and during 24 hours of recovery, the concentration of all oxidative stress indices changed significantly in a way indicating increased oxidative stress in the blood (thiol groups and reduced glutathione decreased, whereas TBARS and plasma antioxidant capacity was increased) as well as in erythrocyte (increased levels of TBARS and protein carbonyls). Erythrocyte antioxidant enzyme activities were also significantly changed by handball. Muscle damage indices (creatine kinase and lactate dehydrogenase) increased significantly after exercise. In addition, IL-6 increased after the game, whereas TNF-a decreased during recovery. Conclusion. This study demonstrates that a single handball game in elite athletes induces a marked state of oxidative stress evidenced by the oxidative modification in plasma and erythrocyte macromolecules, as well as by changes in the enzymatic and nonenzymatic antioxidant system.